The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fnins.2023.1085082
|View full text |Cite
|
Sign up to set email alerts
|

Severe pediatric acute encephalopathy syndromes related to SARS-CoV-2

Abstract: Background and objectivesTo clarify whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection cause acute encephalopathy in children and which are the most common syndromes that cause them and what are the outcomes.MethodsA nationwide web-based survey among all members of the Japanese Society of Child Neurology to identify pediatric patients aged < 18 years who developed acute encephalopathy in Japan between 1 January 2020 and 31 May 2022 associated with severe acute respiratory syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Eleven patients (11/16, recovery, four patients (4/18, 22.2%) died, and 11 patients (11/18, 61.1%) had a neurologic disability. Sakuma et al 21 reported 31 pediatric patients with COVID-19-related ITES (including two ANE cases) and nine patients (29%) had severe neurological sequelae or died. Levine et al 22 summarized 87 cases of non-SARS-CoV-2-induced ANE with a 30% mortality rate and a full recovery rate of less than 10%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven patients (11/16, recovery, four patients (4/18, 22.2%) died, and 11 patients (11/18, 61.1%) had a neurologic disability. Sakuma et al 21 reported 31 pediatric patients with COVID-19-related ITES (including two ANE cases) and nine patients (29%) had severe neurological sequelae or died. Levine et al 22 summarized 87 cases of non-SARS-CoV-2-induced ANE with a 30% mortality rate and a full recovery rate of less than 10%.…”
Section: Discussionmentioning
confidence: 99%
“…After excluding one case without a prognosis report, only 3 patients (3/18, 16.7%) made a full recovery, four patients (4/18, 22.2%) died, and 11 patients (11/18, 61.1%) had a neurologic disability. Sakuma et al 21 . reported 31 pediatric patients with COVID‐19‐related ITES (including two ANE cases) and nine patients (29%) had severe neurological sequelae or died.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, acute encephalopathy constitutes 49% of the neurological symptoms and signs [ 1 ]. Various encephalopathy/encephalitis may arise, including infection-triggered encephalopathy syndrome (ITES), such as acute necrotizing encephalopathy (ANE), acute encephalopathy with biphasic seizures and late reduced diffusion (AESD), encephalopathy with acute fulminant cerebral edema, mild encephalopathy with reversible splenial lesions (MERS), hemorrhagic shock and encephalopathy syndrome (HSES), as well as acute encephalopathy of unknown cause or unclassified, typically occurring during acute febrile illness [ 2 ]. Additionally, demyelination disorders like acute disseminated encephalomyelitis (ADEM) and acute hemorrhagic leukoencephalitis (AHLE) may manifest during both acute and post-infection periods [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 A genetic vulnerability is presumed and can be demonstrated in some patients (such as RANBP2 in acute necrotising encephalopathy), but the majority of patients with ITES do not harbour genetic variants that are measurable in current clinical practise. 2 ITES can occur as a recognisable 'clinico-radiological phenotype', such as acute encephalopathy with biphasic seizures and late restricted diffusion (AESD), febrile infection-related epilepsy syndrome (FIRES), acute necrotising encephalopathy of childhood (ANE), acute fulminant cerebral oedema 3 (AFCE) and mild encephalopathy with reversible splenial lesion (MERS). 1,4 Less common ITES syndromes are acute infantile encephalopathy predominantly affecting the frontal lobes (AIEF) which is a variant of AESD, 5 and hemiplegia hemiconvulsion epilepsy syndrome (HHE).…”
Section: Introductionmentioning
confidence: 99%